Fibula-Assisted Segment Transport (FAST) for Defect Reconstruction after Resection of Tibial Adamantinoma: Report of Two Treatments - A. Rachbauer; A. Laufer; G. Gosheger; G. Toporowski; A. Frommer; E. Jacob; N. Deventer; R. Roedl; B. Vogt (Case Reports in Orthopedics)
Intramedullary limb lengthening via lengthening nails has been performed for more than three decades to overcome leg length inequalities. Plate-assisted bone segment transport (PABST) has recently been described for the reconstruction of segmental bone defects. We modified this procedure by using the ipsilateral fibula as a “biological plate” and report on its technical particularities and application in the reconstructive treatment of adamantinomas of the tibia in two patients. Both patients were successfully treated by wide resection and reconstruction of the tibial bone via bone segment transport through an expandable intramedullary nail using the remaining ipsilateral fibula to provide stabilization and guidance. This procedure was titled “fibula-assisted segment transport” (FAST). This is a new and promising technique that allows an entirely biological reconstruction of large bone defects of the tibia.